Treatment Satisfaction Among Patients Using Anti-Inflammatory Topical Medications for Dry Eye Disease - White DE (Dove Medical Press, 2020)
Darrell E White,1 Yang Zhao,2 Hemalatha Jayapalan,3 Pattabhi Machiraju,3 Ramu Periyasamy,3 Abayomi Ogundele2 1SkyVision Centers, Westlake, OH, USA; 2Sun Pharmaceutical Industries, Inc., Princeton, NJ, USA; 3Indegene, Inc., Bangalore, IndiaCorrespondence: Abayomi OgundeleMedical Affairs, Sun Pharmaceutical Industries, Inc., 2 Independence Way, Princeton, NJ 08540, USAEmail abayomi.ogundele@sunpharma.comPurpose: To assess patient satisfaction among current and former users of the anti-inflammatory topical medications, cyclosporine A 0.05% (CYC) and lifitegrast 5.0% (LIF), for the management of dry eye disease (DED).Patients and Methods: Patients with DED were recruited via physician referral to participate in a survey. Current users of CYC or LIF were asked to rate their experience in terms of satisfaction, side effects, and limitation of activities. Switchers of CYC to LIF or LIF to CYC were asked to rate the importance of potential reasons for switching.Results: Surveys were completed by 207 patients currently treated with CYC (n=98), LIF (n=96), or other DED medications (n=13). Although overall satisfaction with current treatment was high, current users of CYC and LIF reported ineffective relief of DED symptoms (31% and 22%, respectively) and dissatisfaction with the time to onset of effect (29% and 11%). Substantial proportions of patients reported ‘sometimes’, “usually”, or ‘always’ experiencing the following side effects: burning sensation (72% CYC, 64% LIF), itching (43% CYC, 44% LIF), altered sensation of taste (21% CYC, 56% LIF), blurred vision (37% CYC, 50% LIF), and discharge (28% CYC, 30% LIF). Of the 30 switchers of CYC to LIF and 31 switchers of LIF to CYC, the majority reported inability to relieve DED symptoms as a very or extremely important switching reason. Despite switching, one in four patients were somewhat dissatisfied or dissatisfied with their current medication, with 37% of patients reporting ineffective symptom relief.Conclusion: Although the rate of overall satisfaction was generally high with both LIF and CYC, many patients were unable to achieve effective symptom relief and commonly experienced side effects. The proportion of patients who were dissatisfied and/or unable to achieve effective symptom relief even after switching suggests the need for additional treatment options for managing DED.Keywords: patient satisfaction, dry eye disease, cyclosporine, lifitegrast, ocular surface